Solitary Orbital Metastasis in Carcinoma Esophagus: Findings on Serial 18F-FDG PET/CT Scans. (January 2018) - Mahajan, Sonia; Dunphy, Mark P.; Haque, Sofia; Pandit-Taskar, Neeta
Abstract : Abstract: Orbital metastasis is an uncommon and atypical presentation of recurrent esophageal cancer that has been only seldom reported in literature. 18 F-FDG PET/CT is routinely performed for staging and response assessment in patients with esophageal carcinoma. This case demonstrates use of follow-up FDG PET/CT scans in characterizing solitary metastatic disease in orbit and in evaluating response to therapy. It also highlights a key teaching point that postradiation-related inflammatory/infective changes may interfere in accurate assessment of PET/CT scan; however, frequently used clinical and radiological correlation may not be entirely sufficient to rule out pathological involvement.